2023
DOI: 10.1021/acs.jpcb.3c03618
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Novel Fluorescent Nucleobase Analogues Using Computational and Experimental Methods: 2-Amino-6-chloro-8-vinylpurine (2A6Cl8VP) as a Case Study

Nadim Shahriar Russel,
Goutham Kodali,
Robert J. Stanley
et al.

Abstract: Novel fluorescent nucleic acid base analogues (FBAs) with improved optical properties are needed in a variety of biological applications. 2-Amino-6-chloro-8-vinylpurine (2A6Cl8VP) is structural analogue of two existing highly fluorescent FBAs, 2-aminopurine (2AP) and 8-vinyladenine (8VA), and can therefore be expected to have similar base pairing as well as better optical properties compared to its counterparts. In order to determine the absorption and fluorescence properties of 2A6Cl8VP, as a first step, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…In general, fluorophores with tautomeric characteristics are able to promote intramolecular rearrangements upon excitation such as excited-state intramolecular proton-transfer (ESIPT), excited-state intermolecular charge-transfer (ESInterPT) 21,22 or simply phototautomerization of a specific tautomer. 23 The ESIPT and ESInterPT consist of intra- and intermolecular proton transfer processes, respectively, in the excited state of a fluorophore to stabilize the normal locally excited state (LE) (Chart 1A) toward a second excited state called ESIPT (Chart 1A). This excitation mechanism represents an attractive way to not only enhance the fluorescence intensity but also enhance the Stokes shift, which has been widely used in the development of near IR-fluorophores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, fluorophores with tautomeric characteristics are able to promote intramolecular rearrangements upon excitation such as excited-state intramolecular proton-transfer (ESIPT), excited-state intermolecular charge-transfer (ESInterPT) 21,22 or simply phototautomerization of a specific tautomer. 23 The ESIPT and ESInterPT consist of intra- and intermolecular proton transfer processes, respectively, in the excited state of a fluorophore to stabilize the normal locally excited state (LE) (Chart 1A) toward a second excited state called ESIPT (Chart 1A). This excitation mechanism represents an attractive way to not only enhance the fluorescence intensity but also enhance the Stokes shift, which has been widely used in the development of near IR-fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…This excitation mechanism represents an attractive way to not only enhance the fluorescence intensity but also enhance the Stokes shift, which has been widely used in the development of near IR-fluorophores. Meanwhile, the mechanism called phototautomerization consists of simple tautomerization of the excited state toward its corresponding natural and energetically accessible tautomeric form 23 However, a few examples can be found in the literature on phototautomerism and most of them are often mistakenly associated with the ESIPT or ESInterPT mechanisms. 23 a , b Recently, we demonstrated that 3-hydroxy-2-pyrazinecarboxamides present a dynamic enol–keto tautomerism in turn of the 3-hydroxy moiety, which can be consistently modulated toward the keto-tautomer as a function of 6-substitution as follows: 6-F > 6-Cl > 6-Br > 6-I > 6-H and as a function of the solvent environment as follows: H 2 O > MeOH > EtOH > i-PrOH > MeCN > DMSO > DMF > CHCl 3 > n -hexane (Chart 1B).…”
Section: Introductionmentioning
confidence: 99%